The Influence of Macroeconomics Variables on Foreign Direct Investment (Empirical Study From Indonesia) - Nurcahyo, Bagus (Archives of Business Research, 2015)
This paper studies the mutual effects of foreign exchange rate, economic growth and inflation using a case study of Indonesia. By analyzing them we founded that Foreign Exchange Rate, Economic Growth, and Inflation simultanously influence to the FDI in Indonesia. Foreign Exchange Rate and Economic Growth have positive influence to FDI in Indonesia but Inflation has no impact on FDI in Indonesia. It means that FDI in Indonesia depends on Foreign Exchange Rate, Economic Growth. Key Words: Foreign Exchange Rate, Economic Growth, Inflation, FDI, Indonesia